Quarter Life Crisis Shape of Inconsistency of Generation Z Facing Students’ Self Maturation - Markus Asta Patma Nugraha; Slamet Maryoso; Bambang Ismaya (Universitas Muhammadiyah Enrekang, 2023)
Along with the impact received by Indonesia towards the Golden era in 2045, there are phenomena that are considered the impact of luck obtained. The phenomenon that is currently rife is the quarter life crisis. Wilner and Robbin (2001) revealed the concept of quarter-life crisis to the media for the first time from a study process consisting of in-depth interviews with young Americans about their experiences and experiences. The research approach used is a qualitative approach with the method used is a data collection technique consisting of: literature study This research uses literature research methods. By collecting literature data, reading, and recording and processing research materials. Researchers deal directly with existing texts or data and do not conduct field research. In compiling articles, researchers use library data from various sources such as books, journals, articles, official websites, and other internet sources in the form of main material about Quarter Life Crisis is caused by 2 (two) causative factors, namely: (1). Factors from within, (2). Factors from outside oneself. Self-preparation is very important to avoid the acute Quarter life crisis, namely by equipping yourself with soft skills for skill development in yourself and always positioning yourself in a positive environment.